Reproductive history determines Erbb2 locus amplification, WNT signalling and tumour phenotype in a murine breast cancer model - Liliana D. Ordonez; Lorenzo Melchor; Kirsty R. Greenow; Howard Kendrick; Giusy Tornillo; James Bradford; Peter Giles; Matthew J. Smalley (The Company of Biologists, 2021)
Understanding the mechanisms underlying tumour heterogeneity is key to the development of treatments that can target specific tumour subtypes. We have previously targeted CRE recombinase-dependent conditional deletion of the tumour suppressor genes Brca1, Brca2, p53 (also known as Trp53) and/or Pten to basal or luminal oestrogen receptor-negative (ER−) cells of the mouse mammary epithelium. We demonstrated that both the cell-of-origin and the tumour-initiating genetic lesions cooperate to influence mammary tumour phenotype. Here, we use a CRE-activated HER2 orthologue to specifically target HER2/ERBB2 oncogenic activity to basal or luminal ER− mammary epithelial cells and perform a detailed analysis of the tumours that develop. We find that, in contrast to our previous studies, basal epithelial cells are less sensitive to transformation by the activated NeuKI allele, with mammary epithelial tumour formation largely confined to luminal ER− cells. Histologically, most tumours that developed were classified as either adenocarcinomas of no special type or as metaplastic adenosquamous tumours. The former were typically characterized by amplification of the NeuNT/Erbb2 locus; in contrast, tumours displaying squamous metaplasia were enriched in animals that had been through at least one pregnancy and typically had lower levels of NeuNT/Erbb2 locus amplification but had activated canonical WNT signalling. Squamous changes in these tumours were associated with activation of the epidermal differentiation cluster. Thus, in this model of HER2 breast cancer, cell-of-origin, reproductive history, NeuNT/Erbb2 locus amplification and the activation of specific branches of the WNT signalling pathway all interact to drive inter-tumour heterogeneity.